2020
DOI: 10.1111/ene.14335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brain atrophy in patients with multiple sclerosis treated with first‐ versus second‐generation disease modifying therapy without clinical relapse

Abstract: Background and purpose The silent progression of patients with multiple sclerosis (MS) has been reported. The aim of this study was to investigate the association between brain atrophy rates and disease‐modifying drugs (DMDs) in patients with MS during their relapse‐free period. Methods Patients with relapsing‐remitting MS were classified into two groups on the basis of clinical records, i.e. a first‐generation DMD group treated with interferon‐beta‐1a, interferon‐beta‐1b or glatiramer acetate and a second‐gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…30,40 Notably, evidences from comparative studies suggested a higher rate of cortical GM volume change in patients treated with DMF; 13 its capability to reduce brain atrophy loss when compared with other treatments, has been debated. 14,41 Although in line with recent studies suggesting a reduction of neurodegenerative biomarkers in the CSF of patients treated with DMF, 42 the monocenter, not comparative, and relative short-term design of this study prevent a generalization of our results: future multicenter studies with longer follow-up are required to confirm the real neuroprotective effect of DMF.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…30,40 Notably, evidences from comparative studies suggested a higher rate of cortical GM volume change in patients treated with DMF; 13 its capability to reduce brain atrophy loss when compared with other treatments, has been debated. 14,41 Although in line with recent studies suggesting a reduction of neurodegenerative biomarkers in the CSF of patients treated with DMF, 42 the monocenter, not comparative, and relative short-term design of this study prevent a generalization of our results: future multicenter studies with longer follow-up are required to confirm the real neuroprotective effect of DMF.…”
Section: Discussionsupporting
confidence: 53%
“…12 Nevertheless, when compared with other first-line DMTs, DMF showed incresed percentage GM volume loss, but not significant changes in thalamic or deep GM volumes 13 and comparable annualized brain atrophy rates in relapse-free MS patients. 14 All these evidences raise the need to better evaluate the effect of DMF in a relatively large “real-life” cohort of RRMS patients on both focal and diffuse GM pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The two MRI scans (MRI-1 and MRI-2) were selected when the interval between MRI-1 and MRI-2 became larger as much as possible, as reported previously. 16 Because steroids can affect brain volume by causing steroid-related pseudoatrophy, MRIs were excluded when steroid therapy was performed for MS attacks at 60 days before the brain MRI scan, according to previous reports. 17 18 Because patients with AQP4+NMOSD receive prednisolone to prevent the attack, MRIs were excluded when prednisolone pulse therapy was initiated within 60 days before the brain MRI scan.…”
Section: Materials and Methods Study Design And Patient Populationsmentioning
confidence: 99%
“…A previously reported method was used to measure brain volume in each patient. 16 21 Briefly, intracranial volume (ICV) was calculated as the sum of the whole-brain grey matter volume (GMV) plus white matter volume (WMV) and CSF volumes, and this subsequently was treated to normalise for the brain and lesion volumes. Lesions were segmented by the lesion growth algorithm as implemented in the Lesion Segmentation Tool (LST) toolbox V.2.0.15 (available in the public domain at www.statisticalmodelling.de/lst.html ) for SPM.…”
Section: Methodsmentioning
confidence: 99%